2022
DOI: 10.3329/jemc.v10i3.59358
|View full text |Cite
|
Sign up to set email alerts
|

CT-Guided FNAC of Lung Lesions and Cytological Sub-Classification of Bronchogenic Carcinoma of 246 cases at a Tertiary Care Hospital

Abstract: Background: CT-guided fine needle aspiration cytology (FNAC) is a useful tool for evaluating lung nodules or masses. In view of the relative paucity of published studies regionally, this study was undertaken in the Department of Pathology, Enam Medical College & Hospital to see the use of the technique. Materials and Methods: Two forty six CT guided lung FNACs were performed during January 2017 to December 2018 and cytological diagnoses were made. Reported results and relevant data were recorded in the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Present study showed a higher incidence of adenocarcinoma which was like the study of Stewart CJ, et al 16 and Biswas MMA, et al 19 . However, Gouliamos AD, et al 12 found squamous cell carcinoma as the commonest diagnosis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Present study showed a higher incidence of adenocarcinoma which was like the study of Stewart CJ, et al 16 and Biswas MMA, et al 19 . However, Gouliamos AD, et al 12 found squamous cell carcinoma as the commonest diagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…In series based on western populations, TB cases constituted 0.2-1.5% of all FNAC cases for lung nodules 12,22 . In Singapore, TB was found in 5.3% of cases of lung FNAC 19 . In studies from India, the corresponding figures range from 2.1% to 20% 11 .…”
Section: Discussionmentioning
confidence: 99%
“…[11] However, a study conducted by the previous author found more TB cases [7] than this study, which casts some doubt on the lung FNAC method.…”
Section: The Americancontrasting
confidence: 66%
“…[6] The Evidence suggests that FNAC with CT scan can diagnose malignancy in 93−96.6% cases. [7] 100% specificity for a malignant diagnosis by FNAC with CT scan was reported by Sterrett et al in their thoracic review study. [8] Recently, the diagnostic accuracy is reported to be greater than 80% in benign disease and greater than 90% in malignant disease.…”
Section: Introductionmentioning
confidence: 82%